Long-Term Results of Compressive Brace Therapy for Pectus Carinatum - Moon, Duk Hwan; Kang, Min Kyun; Lee, Hye Sun; Lee, Sungsoo (The Thoracic and Cardiovascular Surgeon, 2019)
Background Pectus carinatum (PC) is one of the most common types of congenital chest wall deformity. Recently, noninvasive compressive brace therapy has been more frequently used than invasive surgical correction to treat PC. Hence, the purpose of this study was to determine the long-term outcome of compressive brace therapy.Methods We retrospectively reviewed patients with PC who underwent compressive brace therapy between January 2014 and December 2016. All patients underwent a 2-week compression period, in which braces were worn for 20 hours per day, followed by a 6-month maintenance period, in which braces were worn for 12 hours per day. Patient satisfaction was investigated via telephone survey.Results A total of 320 patients were included in this study. The average age was 13 years, and 280 were males (87.5%). The median follow-up period was 42 months (13–68). Good compliance was observed in 286 patients (89.4%; compliance group). In this group, the initial Haller index significantly increased from 2.20 ± 0.31 to 2.59 ± 0.38 after the 6-month therapy period (p = 0.001). After the 6-month period, 255 patients (89.1%) and 31 patients (12.1%) in the compliance group were very satisfied and satisfied, respectively. Satisfaction at the last follow-up via telephone survey was very satisfied in 250 patients (87.4%) and satisfied in 36 (12.6%). In the compliance group, no patient needed compressive braces again after the therapy period.Conclusion Given the findings presented in this study, compressive brace therapy appears to be a relatively simple and safe method with good long-term outcome in treating patients with PC.
Keywords: chest wall deformity; pectus carinatum; compressive brace